PEMANFAATAN TEKNOLOGI WEB SERVICES PADA PERTUKARAN DATA KATALOG ANTAR PERPUSTAKAAN - Kristiani, Endah (Teknik dan Ilmu Komputer, 2012)
The role of university libraries in the era of information technology advances need to be developed towards the integration of data. Establishment of library networks can be an effective means of learning communities. Problems faced is the interoperability or the ability to integrate different applications in co-operation between libraries in the network. To overcome these problems required Web Service technology, ie technology that can integrate applications, programming languages, and different platforms via http, so that different applications can communicate and exchange data. In this paper, a simulation designed a catalog of data integration between the Library A and Library B. Web Services that bridges the library network is created using PHP using NuSOAP class, while the database used in this simulation is at the Library A MySql Database, and Visual Foxpro Database with ODBC connector on the Library B.Â Keyword: Web service, NuSOAP, integrated online catalogue, interoperability